Microplastics Monitoring in Marine Environment - Agung Dhamar Syakti (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
This review summarizes the need for future spatiotemporal comparisons of microplastic abundance across marine environment, through standardized methods for microplastic sampling and analysis in sea water, beach and seabed sediment and marine organism. Pretreatment of the sample prior to the elimination of organic matter should be done using appropriate reagents was also described. Extraction of microplastics from environmental matrices is based on the different density of targeted microplastics with saturated salt solutions (NaCl, NaI, CaCl2, ZnCl2 and lithium metatungstate). Quantification can be achieved by microscopic techniques (binocular, stereomicroscope, fluorescence microscope and scanning electron microscope) and discussion on identification methods including FTIR, Pyr-GC/MS and Raman spectroscopy will be provided. This review also endorses the importance of further study regarding the fate and impact of microplastics on marine biota and human health, especially when we acknowledge that co-pollution may occur during the transport on microplastic in marine environment.